The effects of lupin (Lupinus angustifolius) addition to wheat bread on its nutritional, phytochemical and bioactive composition and protein quality. (October 2015) - Villarino, C.B.J.; Jayasena, V.; Coorey, R.; Chakrabarti-Bell, S.; Foley, R.; Fanning, K.; Johnson, S.K.
Abstract: The grain legume Australian sweet lupin ( Lupinus angustifolius ; ASL) is gaining international interest as a functional food ingredient; however its addition to refined wheat bread has been shown to decrease bread volume and textural quality, the extent of which is influenced by ASL variety. The present study evaluated the effects of ASL incorporation (20% of total flour) of the six commercial varieties; Belara, Coromup, Gungurru, Jenabillup, Mandelup and Tanjil, on the level of nutritional, phytochemical and bioactive composition and protein quality of refined wheat flour bread. Protein, dietary fiber, phenolic and carotenoid content, antioxidant capacity and protein digestibility corrected amino acid score (PDCAAS) were higher (p < 0.05), whereas available carbohydrate level was lower (p < 0.05) in ASL–wheat breads than the wheat-only bread, regardless of the ASL variety used. In addition, the blood-glucose lowering bioactive peptide γ-conglutin was detected in all ASL–wheat breads but not in wheat-only bread. The ASL variety used significantly (p < 0.05) affected the dietary fiber, fat, available carbohydrates and polyphenolic level, the antioxidant capacity and the PDCAAS of the ASL–wheat breads. These findings demonstrate the potential nutritional and health benefits of adding ASL to refined wheat bread and highlight the importance of selecting specific ASL varieties to maximise its nutritional attributes. Highlights: Nutritional and health-related composition of lupin-wheat breads was evaluated. Lupin addition to wheat bread improved nutritional composition and protein quality. Lupin variety affected bread nutritional and phytochemical composition. Glucose lowering peptide γ-conglutin observed intact in lupin-wheat bread.